Organic Electrochemical Transistors: Ultrahigh‐Gain Organic Electrochemical Transistor Chemosensors Based on Self‐Curled Nanomembranes (Adv. Mater. 29/2021). Issue 29 (20th July 2021) - Ferro, Letícia M. M.; Merces, Leandro; de Camargo, Davi H. S.; Bof Bufon, Carlos C.
Abstract : Achieving synergy between electrochemistry and microelectronics is a hard‐hitting task. In article number 2101518, Carlos C. Bof Bufon and co‐workers employ rolling‐origami nanotechnology to build up novel organic electrochemical transistors (OECTs) featuring outstanding performance. The findings also anticipate that rolling‐origami OECTs are enormously appealing candidates to future applications in chemical and biological sensors (viz., for neurotransmitter detection).